Molecular subgroups of medulloblastoma - Northcott, Paul A.; Pfister, Stefan (Expert review of neurotherapeutics, 2014)
Recent efforts at stratifying medulloblastomas based on their molecular features have revolutionized our understanding of this morbidity. Collective efforts by multiple independent groups have subdivided medulloblastoma from a single disease into four distinct molecular subgroups characterized by disparate transcriptional signatures, mutational spectra, copy number profiles and, most importantly, clinical features. We present a summary of recent studies that have contributed to our understanding of the core medulloblastoma subgroups, focusing largely on clinically relevant discoveries that have already, and will continue to, shape research.